Vitamin D as a central modulator of thyroid diseases: mechanisms and clinical implications - Cheng, Kewen; Hu, Yue; Li, Yuchuan; Zhang, Yi; Wang, Junhui; Zhang, Chunhai (Frontiers in Immunology, 2026)
Thyroid diseases are common endocrine disorders, with the incidence of thyroid cancer and autoimmune thyroid diseases rising worldwide. Vitamin D, a multifunctional steroid hormone, primarily regulates bone metabolism and calcium-phosphorus homeostasis. However, recent evidence increasingly supports the hypothesis that vitamin D plays a central role in the onset and progression of thyroid disorders, including both autoimmune and non-autoimmune conditions. In the present review, we summarize the correlation between vitamin D and thyroid disorders, elucidate the anticancer and immunoregulatory mechanisms of vitamin D in thyroid diseases, and explore its role in modulating gut microbiota. Additionally, we examine the applications in clinical settings of the use of vitamin D supplements in thyroid disorders, such as a preventive measure against cancer development and progression. Clarifying the mechanisms of vitamin D action in the development and progression of thyroid disease will support the design of interventional and early therapeutic strategies that not only prevent disease onset but also serve as a secondary chemopreventive approach to halt progression and enhance thyroid function.